Geopolitical Rivalry and International Legal Order: A Theoretical Examination of Contemporary Power Politics - Imam Syafi'i; Deo Renaldi Saputra (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This article examines how contemporary geopolitical rivalry reshapes the international legal order through normative reinterpretation, selective enforcement, and pluralized economic governance. Employing a non-empirical normative–theoretical methodology, the study integrates doctrinal analysis with structural and critical-constructivist interpretation to assess how great power competition recalibrates foundational legal principles. The analysis demonstrates that sovereignty and recognition doctrines under the United Nations Charter are not eroded but recontextualized within competing geopolitical narratives. Collective security mechanisms exhibit patterns of selective enforcement and discretionary activation, generating legitimacy tensions while preserving institutional continuity. In the economic and technological domains, expansive national security exceptions and regulatory bifurcation illustrate how strategic rivalry restructures treaty interpretation without formally displacing multilateral frameworks. The findings indicate that contemporary power politics embeds rivalry within the operational semantics of international law, producing adaptive constitutional pluralism rather than normative disintegration. International legality emerges as a dynamic equilibrium in which institutional resilience coexists with differentiated application shaped by strategic alignment.